The shack : a novel - Young, William P.; Cummings, Brad.; Jacobsen, Wayne (Los Angeles, CA : Windblown Media, 2007)
After Missy is abducted during a vacation and evidence of her murder shows up at a shack in the forests of Oregon, Mackenzie Philips, her father, receives a strange note inviting him to return to the scene of the tragedy where he wrestles with nightmarish religious questions.
Adult
Adult
Keywords: Life change events -- Fiction; Missing children -- Fiction; Life change events -- Fiction; Missing children -- Fiction; Mystery fiction; Religious fiction; Oregon -- Fiction; Oregon -- Fiction; Religious fiction; Suspense fiction